Ekonomi Keluarga Rumah Tangga Petani di Desa Tembalae Kecamatan Pajo Kabupaten Dompu Nusa Tenggara Barat - Sukrina Sukrina (Rayhan Intermedia, 2018)
This study aims to find out: (1) the conditions and utilization of farmer's land in Tembalae Village, Pajo Sub-District, Dompu District, West Nusa Tenggara, (2) the forms of mutual cooperation between farmer households, and (3) economic management strategies in households and knowing factors. what factors influence the expenditure of farmer households. The type of qualitative research is descriptive research with data collection techniques: observation, interviews, and documentation involving 11 informants. The results of the study show that (1) land ownership through inheritance, purchase, and giving in Tembalae Village has a role in realizing family economic resilience. In the concept of sustainable agriculture, land is a local resource for rural communities. Land, water, relief and land height, climate and cover crops are the basic capital for rural livelihoods (2) mutual cooperation is a characteristic of the general public, so that the nature and existence of mutual cooperation is not just an area. The Tembalae Village community for example, they recognize the existence of mutual cooperation activities with the term (Weha rima) weha rima which is a work that has become their daily activities and is still maintained, and (3) Strategies for managing household economics include strategies for Household Survival Strategy and Consolidation Strategy Household.